Enhanced cell membrane enrichment and subsequent cellular internalization of quantum dots via cell surface engineering: illuminating plasma membranes with quantum dots. Issue 5 (7th January 2016) - Wang, Hong-Yin; Hua, Xian-Wu; Jia, Hao-Ran; Liu, Peidang; Gu, Ning; Chen, Zhan; Wu, Fu-Gen
Abstract : Through hydrophobic interaction-based cell surface engineering, enhanced plasma membrane enrichment and subsequent cellular internalization of quantum dots were achieved. Abstract : Efficient cellular uptake of nanoparticles is crucial for modulating the cell behaviors as well as dictating the cell fate. In this work, by using two commercial reagents (the membrane modification reagent "cholesterol–PEG–biotin" and the avidin-modified quantum dots (QDs) "QD–avidin"), we achieved the enhanced plasma membrane enrichment and endocytosis of fluorescent QDs in cancer cells through cell surface engineering. The QD–cell interaction involved two stages: adsorption and internalization. After incubation with cholesterol–PEG2k–biotin, the cell membrane was engineered with biotin groups that would actively recruit QD–avidin to the cell surface within 1 min. This fast adsorption process could realize high quality and photostable plasma membrane imaging, which is simple, low-cost and generally applicable as compared with the previously reported membrane protein/receptor labeling-based QD imaging. After that, the QDs attached on the cell surface underwent the internalization process and 12 h later, almost all the QDs were internalized through endocytosis. Notably, we found that the internalization of QDs was not via common endocytosis pathways (such as clathrin- or caveolae-mediated endocytosis or macropinocytosis) but more likely via lipid raft-dependent endocytosis. In contrast, without cell surface engineering, the QD–avidin showed negligible cellular uptake. The results demonstrate that cell surface engineering is an efficient strategy to image the plasma membrane and increase cellular uptake of nanoparticles, and will be potentially applied to enhance the efficacy of nanomedicines when therapeutic nanoparticles are used.